Alexander Graham Bell - M Schaefer, Lola (North Mankato, Minnesota Pebble/Capstone Press, a Capstone imprint, 2017)
Simple text and photographs introduce the life of Alexander Graham Bell
A gift from book Africa
Famous people
1 2 13 15
Keywords: Bell, Alexander Graham -- 1847-1922 -- Juvenile literature; Inventors -- Juvenile literature